2017
DOI: 10.3171/2015.12.jns151663
|View full text |Cite
|
Sign up to set email alerts
|

Walking assessment after lumbar puncture in normal-pressure hydrocephalus: a delayed improvement over 3 days

Abstract: OBJECTIVE The determination of gait improvement after lumbar puncture (LP) in idiopathic normal-pressure hydrocephalus (iNPH) is crucial, but the best time for such an assessment is unclear. The authors determined the time course of improvement in walking after LP for single-task and dual-task walking in iNPH. METHODS In patients with iNPH, sequential recordings of gait velocity were obtained prior to LP (time point [TP]0), 1-8 hours after LP (TP1), 24 hours after LP (TP2), 48 hours after LP (TP3), and 72 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 47 publications
(50 reference statements)
1
39
0
4
Order By: Relevance
“…In any case, clarifying the features of ambulatory COM movement in iNPH may help explain the patients' gait and balance disorders and elucidate the appropriate diagnostic and treatment strategies, which may include exercise therapy. Objective gait assessments in patients with iNPH have examined various gait parameters such as temporal and spatial parameters [4][5][6]8,10,[16][17][18][19], but the ambulatory COM movements in iNPH remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In any case, clarifying the features of ambulatory COM movement in iNPH may help explain the patients' gait and balance disorders and elucidate the appropriate diagnostic and treatment strategies, which may include exercise therapy. Objective gait assessments in patients with iNPH have examined various gait parameters such as temporal and spatial parameters [4][5][6]8,10,[16][17][18][19], but the ambulatory COM movements in iNPH remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This observation led us to study the clinical significance of delayed assessment for the prediction of shunt effectiveness. Recently, Schniepp et al reported a delayed improvement over 3 days after CSF removal [10]. Thus, the timing of assessment after CSF removal is an important issue in the tap test.…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al reported that velocity, double support time, and cadence improve significantly after CSF drainage in patients with iNPH in assessments using an instrumented walkway [19]. Schniepp et al also reported an increase in walking speed in various tasks performed on the walkway [10]. They noted maximal improvements of dual task paradigms on days 2 and 3, and recommend that assessments of gait be performed on day 2 or day 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, many other studies recommend examining patients performances since the second day after the CSF-TT [17,19,20,24]. Recently, Schniepp et al examined 24 iNPH patients employing sequential recordings of gait velocity from 1 h to 72 h [25]. The maximal increase was observed in single-tasking after 24 h to 48 h, whereas in dual-tasking after 48 h to 72 h. The low negative predictive value in screening patients for shunting of CSF-TT (37%) might also depend on post evaluations not acquired on the appropriate time point [25].…”
Section: Introductionmentioning
confidence: 99%